Goal-directed self-talk used to self-regulate in male basketball competitions - Latinjak, A. T.; Torregrossa, M.; Comoutos, N.; Hernando-Gimeno, C.; Ramis, Y. (Journal of Sports Sciences, 2019)
This study examined how goal-directed self-talk may help basketball players to self-regulate in stereotypical competitive situations: seconds before a challenging game, while clearly winning or clearly losing, and at the close of a tight game. Participants were recruited in groups of three to four, until preliminary inspection of the data indicated that data saturation was reached. In the end, 34 basketball players voluntarily took part in individual interviews, writing up to three self-instructions they had used in each of the four competitive situations to self-regulate. Content analyses revealed that self-talk in competitive basketball situations serves cognitive functions (e.g., regulating cognition and behaviour), motivational functions (e.g., promoting mastery goals) and emotion and activation-regulating functions (e.g., creating activated states). More specifically, the results also indicated that athletes` self-talk may serve functions specific to the psychological demands experienced in each situation. It is argued that knowing how athletes counsel themselves, could prove important for applied sport psychologists to design psychological skill training.